EFFECT OF DIETARY INCLUSION OF SHEANUT CAKE (VITELLARIA PARADOXA) ON PERFORMANCE OF QUAILS (Indian Journal of Animal Production and Management, 2014)
A trial was conducted on 160 quails to evaluate the level of inclusion of Sheanut cake in the diets using four dietary treatments at (0%) T1, (3%) T2, (6%) T3 and (9%) T4 level of Sheanut cake at Poultry Experimentation Station, College of Veterinary Science Rajendranagar Hyderabad. Significantly (P
Keywords: Anti-nutritive factors; Bodyweight gain; feed conversion ratio; Quail; Sheanut cake